An audit of school oral health education program in a developing country (2014)
The increasing prevalence of oral diseases in children in developing countries is a major public health concern and creates the need to review various preventive strategies put in place on oral health promotion. In the absence of formal national programs, tertiary health institutions have adopted low-budget school oral education programs targeted at improving oral health awareness and behavioral changes in school children. The aim of this study was to review the school oral health education programs conducted by the Community Dentistry Unit of a tertiary hospital in a major city in Nigeria. An evaluation of the school oral health education programs conducted in the city over a 5-year period was done. Data collected included: venue of the program, the number of students and teachers educated in each school, screening and referrals, adequacy of teaching aids, desire for revisit, and barriers noted in its conduct. A total of 104 oral health education programs were conducted during this period involving 16,248 participants. The majority (80%) of the schools visited was primary schools and 54% were privately owned. Over half of the programs were conducted on assembly grounds, 21% in classrooms, and 13% in school halls. Challenges encountered included: lack of audiovisual aids, transportation problems, inadequacy of screening tools, and insufficient promotional materials. All the schools visited requested for (subsequent) regular visitation. Conclusion: The study showed the feasibility of low-budget oral health education and willingness of schools to benefit from such programs. There are barriers to effective communication, which can be mitigated in order to achieve an optimal school oral health education program in a low resource setting